Uji Toksisitas Akut Ekstrak Etanol Daun Manggis (Garcinia Mangostana L.) dengan Melihat Fungsi Hati Tikus Putih Jantan Galur Wistar - Agustina, Inayah Dwi; Setianingsih, Siti; Kaaffah, Silma (Pusat Riset dan Inovasi Nasional, 2025)
Mangosteen (Garcinia mangostana L.) is known to contain various bioactive compounds such as xanthones, flavonoids, and tannins which have great potential as herbal medicine, although its safety aspect still requires further research. This study aims to determine the LD₅₀ value and assess the effect of administering ethanol extract of mangosteen leaves on liver function of male white rats of the Wistar strain using SGOT and SGPT enzyme parameters. Acute toxicity tests were conducted based on the Acute Toxic Class (OECD 423) method by administering the extract orally to two dose groups, namely 300 mg/kgBW and 2000 mg/kgBW, as well as a control group using 1% Na-CMC. The test results showed that at a dose of 300 mg/kgBW no mortality was found in the experimental animals (0%), while at a dose of 2000 mg/kgBW mortality was recorded at 60% (2 out of 3 test animals). The LD₅₀ value cannot be determined precisely due to limited dose variation, but it can be estimated to be in the range of 300–2000 mg/kgBW, in accordance with OECD guidelines that allow reporting of LD₅₀ values ​​in interval form if data are incomplete. Furthermore, liver function tests showed an increase in liver enzyme levels in the 2000 mg/kgBW dose group, where SGOT increased from 42.25 U/L to 74.25 U/L, while SGPT increased from 35.25 U/L to 52.25 U/L, although these values ​​are still within the normal physiological range. Thus, mangosteen leaf extract shows potential toxicity at high doses, so its use as a herbal medicine still requires further study.